Analysis of Shariah Compliant E-Commerce Models on the C2C business model at Tokopedia Salam - Ahmad Hanafi; Khairil Anwar Al-Banjari; Taufik Warman Mahfuz (Pelopor Publikasi Akademika, 2022)
Tokopedia online store launched a new feature, namely Tokopedia Salam. This feature is the first e-commerce in Indonesia to make it easier for people to fulfill a variety of daily needs with a wide selection of halal products and services that are good, more complete and trustworthy. Tokopedia Salam means Tokopedia Bai As-Salam, which means that transactions that occur at Tokopedia Salam should be in accordance with Shariah compliance. The purpose of this study was to identify and describe the Tokopedia Salam business model with the suitability of the sharia e-commerce compliance model. This study uses a qualitative method, namely research that aims to describe the phenomenon and context in the business transaction model at Tokopedia Salam with a fiqh approach. Data was collected by means of observation, interviews and documentation studies. The results of this study indicate that the business transaction model at Tokopedia Salam is in accordance with the sharia e-commerce compliance model. This can be seen by the presence of: a. The transaction agreement or contract used is in accordance with sharia provisions; b. Transactions between sellers and buyers reach an agreement on a consensual basis c. The object or product has clear information and the transaction price is paid in cooperation with Islamic banks and; d. Free from various transactions that are prohibited in Islam (riba, maysir, gharar, ikrah and haram).